(untitled) (Eurasian Scientific Herald, 2024)
In this article, Sayyadi’s ability to use words is studied on the example of the use of artistic image tools in the epic of Tahir and Zuhro. In the article, art forms such as allusion, exaggeration, and proverb are separately researched as means of Sayyadi’s individuality in using words in their own and figurative sense. This research serves to reveal more clearly the essence of the studied romantic epic and to illuminate its unique aspects. In the article, the issues of folklore traditions in Sayyadi’s epic "Tahir and Zuhro" are widely covered, with a comparative study of examples of folk oral creativity. The role of masnavi, mukhammas and ghazal genres in the composition of the epic, the characteristics of the image style in it, as well as Sayyadi’s skill in using artistic image tools such as tashbih, exaggeration, and irsol ul-masal, based on examples taken from the epic "Tahir va Zuhra" analyzed